BIM-enabled collaborative scaffolding scoping and design - Wang, J.; Chi, Hung-Lin; Liu, C.; Wang, Xiangyu (2016)
Scaffolding management is critical to construction industries across the oil and gas, building, and infrastructure sectors, where static and ineffective design and planning can lead to low productivity and cost issues. In addition, the requirement analysis of scaffolding scoping seriously relies on the quality of the communication between scaffolding supervisors and owners. To avoid unnecessary disputations, the aim of this research is to develop a Collaborative Scaffolding Scoping and Design Platform (CSSDP) to facilitate the communication among different trades, and engage their expertise to comment, review and improve the design scheme from the end-user perspective. The proposed CSSDP includes three main modules: mobile application, cloud server and management dashboard. In addition, four styles of comments will be embedded into the mobile application, namely, text, voice, image-based sketching, and Building Information Modelling (BIM) model-based sketching. The implementation and evaluation of the user interface and commenting functions have been finished, and the prototype of the application is integrated into the proposed CSSDP. The outcomes of internal workshops conducted through industrial partners show positive responses and further investigations for experimental adaption are expected in the near future.